ANALISIS PENYELENGGARAAN PEMERINTAHAN PASCA PEMEKARAN DI KELURAHAN SEMPAJA TIMUR KOTA SAMARINDA - Vina Karmilasari (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The purpose of this study is to describe and to analyze government implementation after developing in political district east sempaja. This study used descriptive qualitative approach, with data collection technique by observation, interview, and study of documentation, and they were analyzed by using analysis technique of interactive model data, through, step of data condensation, data presentation, and determine conclusion/ verification. Data validity testing used technique of source triangulation credibility test. The result of this study showed that government implementation after developing in political district east sempaja looked from political district function in doing the task government affair implementation, development, and social showed that all of those function have been done but in doing it still got obstacle and obstruction because of lacking coordination and preparation in doing government administration process after developing between government of political district east sempaja and other institution.Keyword: implementation, political distric government, after developing